Hypoxia-inducible factors: details create a picture. Part I. HIF-1 - G. A. Ignatenko; N. N. Bondarenko; S. V. Tumanova; T. S. Ignatenko; A. A. Kaluga; Ya. S. Valigun (Фундаментальная и клиническая медицина)
The review presents a comparative analysis of scientific data on the structural and functional characteristics of subunits (HIF-1α and HIF-1β) of hypoxia-inducible transcription factor-1 (HIF-1). Differences between the main regulatory HIF-1α subunit and the constitutively expressed HIF-1β subunit, sensitivity to endo- and exogenous regulators of their stability, and intracellular content depending on the cell's oxygen supply state (normoxia and hypoxia conditions) are described. In normoxia, the intracellular content of HIF-1α is determined by oxygen-dependent and oxygen-independent mechanisms. Oxygen-dependent enzymatic degradation of HIF-1α occurs by PHD-dependent hydroxylation, VHL-dependent ubiquitination, and FIH-1-dependent hydroxylation. Oxygen-independent pathways of HIF-1α pool regulation include: 1) HIF-1α gene transcription (Notch and/or NF-KB-dependent, STAT3 and Sp1 cytokine-dependent), 2) mRNA translation (cap-dependent or IRES-dependent, as well as cytokine-dependent activation of the PI-3K/AKT pathway activation under the effect of growth factors and vasoactive hormones), 3) protein-protein interactions, 4) various mechanisms of post-translational modification. Changes in Krebs cycle enzyme activity and active oxygen forms confer HIF-1α stability through PHD activity inhibition and reduction of ubiquitin-proteasome degradation. PHD-independent post-translational stabilizers of HIF-1α are: cytosolic reductase NQO1, sirtuin-2, prostaglandin E2, activated protein kinase C1 receptor competing with heat shock protein 90, human Hdm2 (a natural inhibitor of p53), glycogen synthase kinase 3β, and negative modifiers are enzymes - methyltransferase SET7/9, lysine-specific demethylase-1, sex-like kinase 3, β-arrestin-2, casein kinase-1. Under hypoxic conditions, non-hydroxylated HIF-1α subunits migrate to the nucleus where they heterodimerize with HIF-1β, HIF-1α/β heterodimers bind the main 5'-(A/G)CGTG-3' consensus sequence within the hypoxia-reaction element (HRE) of the target genes, and recruit co-activators (p300, histone modifying enzymes, histone readers, chromatin remodeling proteins, and mediator proteins for target genes transcription enhancement with the aid of RNA polymerase II), resulting in the formation of HIF-1, acting as a transcription factor for the target genes providing metabolic reprogramming from oxidative phosphorylation to anaerobic glycolysis (genes encoding glucose transporters (GLUT1 and GLUT3), genes for glycolytic enzymes hexokinase 1 and 2 (HK1 and HK2), phosphoglycerate kinase 1), as well as genes for erythropoietin, vascular endothelial growth factor and its receptors FLT1 and FLK1, endothelin 1 and angiopoietin 1, resulting in adaptation to hypoxia.